Teaching Analytics and Digital Media to Advertising Students. (May 2021) - Brown-Devlin, Natalie
As the advertising industry continues to list analytical reasoning as a necessary skill for employment, more universities are including analytics into their advertising curriculum. This article outlines how I teach an analytics-focused course in a top-ranked advertising program. In this article, I briefly summarize each course module and describe a variety of assignments that are used to meet each learning objective. I also provide citations and links to resources, datasets, and software that I currently use in hopes of helping other professors locate resources that have proven quite helpful for teaching analytics content to advertising students.